THE IMPACT OF TASK BASED LEARNING ON STUDENTS’ SPEAKING SKILLS - Aliyeva Diyora; Xasanova Xurshida (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The effect of Task-Based Learning (TBL) on students' speaking abilities in EFL classes is examined in this paper. TBL stresses effective interaction via actual assignments, in contrast with typical grammar-focused training. According to the study, TBL increases communicating abilities, lowers anxiety, and promotes the ease of speaking. Students get confidence and real-world speaking expertise by participating in engaging group activities. All things considered, task-based learning is a successful method for improving oral proficiency.